Nokia Product Life Cycle / Christina Tony ... [et al.] - Tony, Christina; Allias, Nor Affida; Winston Rajit, Tiffany Amber Belantau; Hossain, Nur Hafizah; Daniel, Benjamin Danrie (2014)
Nokia is the world's largest manufacturer of mobile phones. As far as the market share is concerned, it has a global market share of 36 percent in the first quarter of year 2007. This largest handset manufacturer produces mobile phones for each major market and protocol. Espoo, a city closed to Helsinki, Finland, is the headquarters of Nokia. Apart from that, it has a manufacturing, R&D and sales representation in many countries. Nokia is the best and largest Finnish company and it accounts half of the market capitalisation of the Helsinki Stock Exchange. It is the world's 274th-largest company measured by 2013 revenues according to the Fortune Global 500. The company is a component of the Euro Stoxx 50 stock market index. The company has had various industries in its 150-year history, originally founded as a pulp mill, and currently focuses on large-scale telecommunications infrastructures, and technology development and licensing. Nokia is also a major contributor to the mobile telephony industry, having assisted in development of the Global System For Mobile Communication (GSM) and Long Term Evolution (LTE) standards, and was, for a period, the largest vendor of mobile phones in the world. Nokia's dominance also extended into the smartphone industry through its Symbian platform, but was soon overshadowed by competitors. Nokia eventually entered into a pact with Microsoft in 2011 to exclusively use its Windows Phone platform on future smartphones. Its mobile phone business was eventually bought by Microsoft in an overall deal totaling $7.17 billion. Stephen Elop, Nokia's former CEO, and several other executives joined the new Microsoft Mobile subsidiary of Microsoft as part of the deal, which was completed on April 25, 2014.